Topologically massive yang-mills field on the null-plane: A hamilton-jacobi approach - Bertin, M. C. [UNESP]; Pimentel, B. M. [UNESP]; Valcárcel, C. E. [UNESP]; Zambrano, G. E R (AIP Publishing, 2010)
Non-abelian gauge theories are super-renormalizable in 2+1 dimensions and suffer from infrared divergences. These divergences can be avoided by adding a Chern-Simons term, i.e., building a Topologically Massive Theory. In this sense, we are interested in the study of the Topologically Massive Yang-Mills theory on the Null-Plane. Since this is a gauge theory, we need to analyze its constraint structure which is done with the Hamilton-Jacobi formalism. We are able to find the complete set of Hamiltonian densities, and build the Generalized Brackets of the theory. With the GB we obtain a set of involutive Hamiltonian densities, generators of the evolution of the system. © 2010 American Institute of Physics.
Keywords: Hamilton-Jacobi formalism; Topologically Massive Yang-Mills